Effect of Salam leaf extract (Syzygium Polyanthum) to serum IL-10 levels on Acute Coronary Syndrome in Wistar Strain Mice Model - Tanjung, Yulisa Astari; Refli Hasan; Rahmad Isnanta (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Background Coronary Heart Disease (CHD) is one of the leading causes of death in developed and developing countries. Â Syzygium polyanthum leaf (daun salam) are reported to have anti-inflammatory, antioxidant, antidiabetic, antimicrobial, antihypertensive, antitumor, antidiarrheal, acetylcholinesterase inhibition, and lipase inhibitory activity. The purpose of this study was to prove the effect of bay leaf extract (Syzygium polyanthum) on serum interleukin (IL)-10 levels in the heart of Wistar Strain Mice Model of Acute Coronary Syndrome (ACS). Methods This is an experimental study to compare the IL-10 level in 32 ACS mice which were divided into 8 groups. Serum IL-10 values were collected and analyzed according to the corresponding group with and without bay leaf extract administration, on day 1,4,7, and 14. Result: There is an IL-10 value increasing with the duration of examination following the onset of ACS induction. The highest average IL-10 value was found on the 14th day, in the two groups. On the same day, it was seen that the treatment group had a higher IL-10 value compared to the control group (p<0.001). The result showed that the concentration of IL-10 was significantly greater among the treatment group, which Â reveal the potential benefit of bay leaf extract in patients with ACS. Conclusion: There was found a significant difference of serum IL-10 between Wistar Strain Mice Model of ACS that was given S. polyanthum leaf extracts. S. polyanthum leaf extract has quite extensive benefits in the cardiovascular system.